AKUNTABILITAS KELEMBAGAAN EKSEKUTIF - Gedeona, Hendrikus Triwibawanto (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2007)
Accountability is one among preresequistes for building good government. It exemplifiesgood morale, ethics and social responsibility of the government to its citizens. Effectiveand sustainable government accountability becomes visible when the governmentpromotes public control and participation based upon the principles of democracy andgood governance.